Solute-water interactions in the aquation of Isonicotinohydrazide and nicotinic acid complexes of pentacyanoferrate(n) at various pH - Blesa, Miguel A.; Funai, Irene A.; Morando, Pedro J.; Olabe, José A. (Royal Society of Chemistry, 1977)
Fil: Blesa, Miguel A. Comisión Nacional de Energía Atómica; Argentina